How to Avoid Compensating CEO for Luck: The Case of Microeconomic Fluctuations - Lars Oxelheim; Clas Wihlborg; Jianhua Zhang (Research Institute of Industrial Economics (IFN), 2010)
Incentive effects of performance-based compensation schemes for management may be weakened or biased by macroeconomic influences on remuneration. These influences can be seen as reflecting luck from the CEOs perspective. In this chapter we present a model for how to avoid compensating CEO for luck by filtering out the macroeconomic influences. In the empirical section we analyze the impact of macroeconomic, industry and firm-specific factors on the compensations (salary, bonus, options, and pensions) of CEOs in 127 Swedish corporations during the period 2001-2007. We find macroeconomic influences on Swedish CEOs compensation to be substantial. Distinguishing between favorable and unfavorable macroeconomic developments, we find compensation to be more responsive to favorable than to unfavorable developments in macroeconomic variables.
Keywords: L14; L16; M14; M21; M52; 330; Executive compensation; Salary; Bonus; Option; Pension; Macroeconomic uncertainty; Macroeconomic factors; Performance; Luck; Führungskräfte; Vergütungssystem; Leistungsentgelt; Aktienoption; Konjunktur; Wirtschaftsindikator; Schweden